The cost‐effectiveness of contemporary home haemodialysis modalities compared with facility haemodialysis: A systematic review of full economic evaluations. Issue 8 (August 2014) - Walker, Rachael; Marshall, Mark R; Morton, Rachael L; McFarlane, Philip; Howard, Kirsten
Abstract Aim The financial burden of the increasing dialysis population challenges healthcare resources internationally. Home haemodialysis offers many benefits over conventional facility dialysis including superior clinical, patient‐centred outcomes and reduced cost. This review updates a previous review, conducted a decade prior, incorporating contemporary home dialysis techniques of frequent and nocturnal dialysis. We sought comparative cost‐effectiveness studies of home versus facility haemodialysis (HD) for people with end‐stage kidney failure (ESKF). Methods We conducted a systematic review of literature from January 2000–March 2014. Studies were included if they provided comparative information on the costs, health outcomes and cost‐effectiveness ratios of home HD and facility HD. We searched medical and health economic databases using MeSH headings and text words for economic evaluation and haemodialysis. Results Six studies of economic evaluations that compared home to facility HD were identified. Two studies compared home nocturnal HD, one home nocturnal and daily home HD, and three compared contemporary home HD to facility HD. Overall these studies suggest that contemporary home HD modalities are less costly and more effective than facility HD. Home HD start‐up costs tend to be higher in the short term, but these are offset by cost savings over the longer term. Conclusions Contemporaneous dialysis modalities including nocturnal and daily home haemodialysis are cost‐effective or cost‐saving compared with facility‐based haemodialysis. This result is largely driven by lower staff costs, and better health outcomes for survival and quality of life. Expanding the proportion of haemodialysis patients managed at home is likely to produce cost savings.